Framing of terrorism and Ethiopian dam on online Egyptian publications and social media - El Tawil, Noha (AUC Knowledge Fountain, 2018)
This study aims at examining the framing of crises threatening the security and welfare of Egypt embodied in the ongoing terrorism and the construction of the Grand Ethiopian Renaissance Dam (GERD) that will drastically decrease the country's water share. The samples are derived from social media, specifically Facebook and Twitter, as well as online publications. The nine political Facebook pages selected are among the top 100 in Egypt in terms of followers. The three publications are chosen to reflect the type of ownership which varies from state-owned to privately-owned including partisan publications. The Tweets were picked according to hashtags of incidents that occurred within the time frame extending from September 2017 till March 2018. Those tweets had to be by citizen users and not professional publications or public figures. The study looks into types of frames, and stereotypical frames, as well as, rumors promoted to be bases for determining the master and tactical frames adopted by each political group on each topic. The theoretical framework is Framing Theory, Public Sphere Theory and Two-step-flow Theory. The research method used is content analysis to study social media posts, tweets, and online publications' op-eds collected through purposive sampling. For terrorism, the time frame included three major terror attacks publicly known as the Rawda Mosque Attack in North Sinai, the Wahat Incident, and Helwan Church. As for the Ethiopian dam, the time frame consisted of failure in technical negotiations throughout different rounds, and a great progress in the dam's construction. The research at hand draws a clear image of the dominant frames adopted by different political groups, and to what extent stereotypical frames and rumors were deployed to communicate different messages serving the master and tactical frames such groups adopt.